Mosque-Based Community Empowerment to Improve Clean and Healthy Living Behaviors for Stunting Prevention - As-sa'diah, Dini; Ariqi, Muhammad Nafis; Saputra, Nofrans Eka (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2026)
The risk of stunting and the low level of Clean and Healthy Living Behaviors (CHLB). The adoption of clean and healthy living behaviors (CHLB) remains a major public health challenge.  This program, which is based in the mosque, was designed to strengthen community awareness and encourage active participation in CHLB practices. The main partners involved include the local community, DKM (Dewan Kemakmuran Masjid), mosque youth groups, and health cadres in Kelurahan Tahtul Yaman. The program was carried out through several approaches, including education sessions, hands-on training, cadre development, and environmental actions through an integrated cleanliness movement. Overall, the program achieved its intended targets and led to a noticeable increase in community participation. One of the key outcomes was the formation of twelve youth health cadres who are now able to carry out various health-related activities, such as creating 30 biopori holes, producing natural soap, and providing cleanliness boxes in the mosque. In addition, community understanding of CHLB (Clean and Healthy Living Behavior) and stunting prevention has improved. More importantly, the program helped build greater awareness about health issues and contributed to a cleaner and healthier environment, supported by active involvement from the community.